Task sharing for point-of-care testing: Review of national health policies and implementation landscape in 19 African countries - Zibusiso Ndlovu; Mariamo Ibraimo Assane; Francis Ocen; Ki-zerbo Charles Lamou; Musonda Mandona; Fingani Annie Mphande; Emmanuel Kabwe; Noah Takah Fongwen; Halifa Mbae Said; Omolara Emmanuel; Emeka Elom; Sandra Chipuka; et al. (PLOS Global Public Health, 2025)
World Health Organization recommends task sharing (TS) for point-of-care testing (POCT) with lay health workers (LHW) to improve access when professional capacity is limited. Despite many benefits of POCT, TS remains underutilized. This study examined uptake of TS for POCT in national policies and the implementation landscape in 19 African countries from November 2024 to March 2025. A mixed-methods approach included an online cross-sectional survey with stakeholders (national ministries of health, medical associations, private laboratories, implementation supporting partners, LHWs); review of national health strategic and policy documents and key informant interviews (KII) with national laboratory directors. Standardized emails recruited participants, whilst documents came from requests and online searches. Quantitative data were analysed descriptively, and KII data with framework analysis. Of 217 policy documents collected, 197 (91%) were relevant. Over half of national health strategic plans (10/19; 53%) recognize LHWs as vital for expansion of primary healthcare services, but fewer (7/19; 37%) mention TS. While 58% (11/19) of national laboratory strategic plans aimed to expand POCT access and quality, 84% did not mention LHW to support TS. Among national HIV/AIDS strategic plans, 53% (9/17) referenced TS for POCT, mainly for HIV diagnosis; with only one addressing POCT for advanced HIV disease. Outside HIV and malaria, LHW POCT was rarely emphasised in disease-specific strategic plans. Seventy-five stakeholders (67% male) completed the online survey, and six KII were conducted. All reported that LHW conduct POCT, mainly with donor-support. HIV rapid testing was cited as having the most structured training program. National laboratory leaders acknowledged implementation challenges but saw opportunities to expand LHW-led POCT. Shifting from fragmented, disease-specific approaches to multi-disease TS model is crucial for sustainable POCT. Coherent policy and implementation reforms are needed to institutionalize TS amid declining resources. National laboratory leadership should drive the adoption of training and quality assurance for TS for multi-disease POCT.
Keywords: Global Health and Surgery; HIV/AIDS Research and Interventions; Global Maternal and Child Health